Control Methods and Influence Factors of Silt Liquefaction: Case of the Wangqingtuo Reservoir in the South-North Water Diversion project (Tianjin, China). Issue 5 (March 2019) - Mark Tambatamba, Mulunda; Che, Ailan; Zhu, Renjie
Abstract: Soil liquefaction is a major cause of site damage to an earth dam in the earthquake and geotechnical engineering. Wangqingtuo Reservoir is an integral part of China's South-North Water Transfer Project in Tianjin. Due to the weak geological engineering conditions of the reservoir area and the location belonging to regions with basic earthquake intensity of degree 7, there is a slight possibility of liquefaction of the dam foundation, when the reservoir is impounded. Therefore, liquefaction control measures need to be implemented. Mainly by improving soil properties and initial stress of the liquefiable soil, four liquefaction control measures were put forward; surface excavation and backfilling, setting pressure platforms, anti-seepage platform and strengthened drainage design. Based on high-density surface wave exploration, field tests, laboratory tests, liquefaction identification, and liquefaction classifications; influence factors of silt liquefaction are determined with results analyzed before and after liquefaction control measures of the dam structure. A dynamic numerical modeling analysis was used to evaluate the extent of the liquefaction control measures, with the aid of Geo-slope software.